Terrestrial nanoparticle contaminants and geospatial optics using the Sentinel-3B OLCI satellite in the Tinto River estuary region of the Iberian Peninsula (2023)
The Tinto River is known globally for having a reddish color due to the high concentration of dissolved metals in its waters. The general objective of this study is to analyze the dispersion of nanoparticles (NPs) and ultra-fine particles in terrestrial and geospatial suspended sediments (SSs) using Sentinel-3B OLCI (Ocean Land Color Instrument) satellite images; by examining water turbidity levels (TSM_NN), suspended pollution potential (ADG_443_NN) and presence of chlorophyll-a (CHL_NN). The images were collected in the estuary of the Tinto River, in the city of Nerva, Spanish province of Huelva, between 2019 and 2021. The following hazardous elements were identified in nanoparticles and ultra-fine particles by FE-SEM/EDS: As, Cd, Ni, V, Se, Mo, Pb, Sb and Sn. Sentinel-3B OLCI satellite images detected a 2019 TSM_NN of 23.47 g−3, and a 2021 reading of 16.38 g−3.